Transposon mutagenesis of atypical enteroaggregative Escherichia coli reveals a hemagglutinin-associated protein that mediates cell adhesion and contributes to the Galleria mellonella virulence - Monfardini, Mariane V.; Souza, Renata T.; Rojas, Thais C. G.; Guerrieri, Caroline G.; Orikaza, Cristina; Scaletsky, Isabel C. A. (Frontiers in Cellular and Infection Microbiology, 2023)
Twenty-two atypical enteroaggregative Escherichia coli isolates from previous epidemiological studies harboring chromosomal and plasmid EAEC virulence genes were examined for their adhesion properties. Nine strains showed a typical AA pattern, while 13 strains showed variants of AA, such as an AA with lined up cells characteristic of the chain-like adhesion (CLA) and an AA with adherence predominatly to HeLa cells characteristic of the diffuse adherence (DA). The AFP-encoding genes (afpA1 and afpR) were detected only in strain Q015B, which contained the plasmid genes shf, astA and pet and the chromosomal genes aaiC and set1A and displayed an AA/DA pattern. Using Tn5-based transposon mutagenesis on Q015B strain, we identified a 5517-bp open reading frame (ORF) encoding a predicted 1838-amino-acid polypeptide that is genetically related to a putative filamentous hemagglutinin identified in E. coli strain 7-233-03_S3_C2. Therefore, the ORF was named Eha. The regions flanking Eha were sequenced and two ORFs were found; upstream, an ORF that encodes a 603-amino-acid polypeptide with 99% identity to hemolysin secretion/activation proteins of the ShlB/FhaC/HecB family, and downstream, another ORF, which encodes a 632-amino-acid polypeptide with 72% identity to the glycosyltransferase EtpC. An eha mutant (Q015Beha) was obtained from strain Q015B. Q015Beha strain did not adhere to HeLa cells, whereas Q015Beha transformed with a pACYC184 plasmid carrying eha restored the phenotype. Furthermore, the Q015eha mutant had a marked effect on the ability of strain Q015B to kill the larvae of Galleria mellonella. Our results suggest that Eha contributes to cell adherence and virulence of Q015B strain.